Handbook of research on curriculum reform initiatives in English education - Denman, Christopher; Mahrooqi, Rahma al- (IGI Global, 2019)
"This book details the latest theoretical and methodological approaches in curriculum reform in English education from a variety of perspectives, but also offers examples of the research that both builds upon these theories while simultaneously driving understanding and practice in this area"...
Includes bibliographical references
Keywords: English language -- Study and teaching -- Foreign speakers -- Curricula